Gautama Buddha in life and legend. - Kelen, Betty (New York, Lothrop, Lee & Shepard Co., 1967)
Combines archeological fact and Buddhist theological legend to recount the life of Gautama Buddha, from the traditional story of his birth, through his quest for wisdom, the years as a sage and teacher, and his death.
Bibliography: p. [187]-188.
Keywords: Gautama Buddha; Buddha; Buddhism